2015
DOI: 10.5371/hp.2015.27.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Atypical Femoral Fracture-like Fracture after Hip Arthroplasty: A Report of Three Cases

Abstract: Atypical femoral fractures are stress or insufficient fractures induced by low energy trauma or no trauma and have specific X-ray findings. Although the American Society for Bone and Mineral Research has excluded periprosthetic fractures from the definition of an atypical femoral fracture in 2013, this is still a matter of controversy because some authors report periprosthetic fractures showing specific features of atypical fractures around a well-fixed femoral stem. We report 3 cases of periprosthetic femur f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…callus and disappearing fracture line at 4 months postoperatively, and the patient was able to walk without assistance or thigh pain. Similar cases have been reported (Table 1) [3][4][5][6][7][8][9][10][11][12]. All were females and all had a history of long-term bisphosphonate therapy.…”
Section: D B a B Asupporting
confidence: 77%
“…callus and disappearing fracture line at 4 months postoperatively, and the patient was able to walk without assistance or thigh pain. Similar cases have been reported (Table 1) [3][4][5][6][7][8][9][10][11][12]. All were females and all had a history of long-term bisphosphonate therapy.…”
Section: D B a B Asupporting
confidence: 77%
“…The minor features include a generalized increase in cortical thickness of the femoral diaphysis, prodromal symptoms such as thigh pain, a bilateral incomplete or complete femoral diaphysis fracture, and delayed fracture healing. However, periprosthetic fracture is excluded from this definition, 8,9 but in some cases, specific features of AFFs have been observed around the periprosthetic region, [10][11][12] as was also the case here. Although this kind of fracture is not included in the AFF definition, it may have the same or similar pathology.…”
Section: Discussionsupporting
confidence: 52%
“…Cross et al reported incomplete PAFFs treated by discontinuing BPs, starting teriparatide, and limiting weight bearing [ 4 ], while Bhattacharyya et al reported successful treatment of incomplete PAFFs by only discontinuing BPs and limiting weight bearing [ 8 ]. Lee et al reported preventive osteosynthesis surgery performed for a case in which femoral pain and fracture lines were revealed despite loading restriction and teriparatide administration for incomplete PAFFs [ 10 ]. Robinson et al reported a comparative series of 10 cases of PAFFs and 12 cases of AFFs and found clinically significant differences in time to union, mortality, and complications.…”
Section: Discussionmentioning
confidence: 99%